Pengembangan E-Modul Ansambel Musik Berbasis Project Based Learning di Kelas IV Sekolah Dasar - Dinda Maharani; Desyandri (UNIB Press, 2024)
Technological developments have greatly influenced the world of education, including the implementation of the learning process in schools. However, in its application in the field, learning integrated with technology has not been implemented optimally. Based on preliminary studies that have been carried out, teachers only use conventional teaching materials which makes students not enthusiastic about participating in the learning process. The use of E-Modules in implementing IT-based learning is one solution to this problem. This research was carried out with the aim of developing a Music Ensemble E-Module Based on Project Based Learning in Elementary Schools. This research uses an R&D (Research & Development) approach with the ADDIE research model. From the results of the E-Module validity trial on the material, language and media aspects, an average score of 93.3% was obtained in the very valid category. Then with an average of 97.86% and 95.32% for teacher and student practicality responses, in the very practical category. The results of the effectiveness of the E-Module are an average of 93%, in the very effective category. Thus, the E-Module for musical ensembles based on project based learning in elementary schools has been proven to be valid, practical and effective teaching material.